Business Strategy for Religious Tourism in Mount Haruman, Indonesia - Dini Turipanam Alamanda; Ikeu Kania; Rahyuniati Setiawan; Selvi Silfiani Rahayu (Iapa Proceedings Conference, 2020)
This study is aimed at investigating the strategy formulation in the development of religious tourism in Mount Haruman by using a SWOT analysis and Quantitative Strategic Planning Matrix (QSPM). The latter was used to determine the recommended strategies to be implemented. The research employed a descriptive qualitative research with a case study approach. The data were collected by using in-depth interviews and distributing questionnaires to a number of key informants around Mount Haruman. The results showed that there were a number of alternative strategies used. The religious tourism managers of Mount Haruman were able to develop their natural potential by holding special events, providing navigation, increasing promotion, providing and developing various facilities, improving the quality of human resources, establishing cooperation and community ownership, planning and developing tourism, maintaining and repairing infrastructure, as well as improving visitor awareness. Based on the analysis of all alternative strategies through QSPM, the strategy that should be implemented and treated as a top priority is to increase promotion. It can be carried out by utilizing information and communication-based technology that is currently developing. The study brings implication that information technology plays a crucial role in tourism development, especially in religious tourism in Mount Haruman.